Adoptive Transfer of Immune Response in a Xenogenic System (London Journal of Medical and Health Research, 2025)
Rupert Billingham, Leslie Brent and Peter Medawar showed in 1953 that the state of sensitization to an antigen could be passively transferred to a recipient with a transplant of specifically sensitized donor lymphoid cells, which continued to function successfully in their new body [1]. This transfer of immunity was designated by R. Billigham and co-authors [2] as adoptive transfer, and the immunity itself was called adoptive or perceived immunity.Adoptive transfer of lymphocytes is currently used to assess the functional activity of individual cell forms or to develop cell therapy techniques, for example in experimental oncology, using T-lymphocytes specifically sensitized to tumor antigens [3, 4, 5, 6, 7]. However, the problem of adoptive transfer of immune response remains far from being resolved. It is believed that adoptive transfer of sensitization to a specific antigen is possible only through the introduction of lymphoid cells of an immunized donor to the recipient [8, 9, 10, 11].We have previously shown that adoptive transfer in a syngeneic system (BALB/c mice) can also be accomplished via platelets [12 ]. In the available literature, we have not found information on the possibility of adoptive transfer of sensitization via platelets in a xenogenic system. In this regard, the goal of the present study was chosen.